Light and lively : a reader - Felder, Mira B. (Harcourt, Brace, Jovanovich, 1979)
{09}This book have annotated bibliography of high-interest, low-reading-level fiction and nonfiction materials around themes that appeal to adults. Covers a variety of resources, from books and chapters of books to magazine articles and letters, organizing them from easier to more difficult reading levels to help readers progress with their reading. Dozens of dialogue and writing activities are suggested for each subject area. Perfect for adult and family literacy programs, ESL students, teen remedial reading classes, and readers' advisory, this book is a great tool for motivating and empowering students to read.